Numerical simulation of flows in designed sleeve models at distal anastomoses - Tong, Jia Hui (2008)
This thesis consists of two (2) parts - Part A -. The focus of this research is to design and evaluate sleeve models with cuff-like geometries of varying volume as well as out-of-plane and bypass angles. Sleeve models exhibiting optimized hemodynamics can be used as mechanical connectors between the bypass graft and host artery at the distal anastomosis, hence eliminating the need for suturing.